Studies on the Development of Value Added Guava- Mint- Basil- Honey Blended Ready to Serve Refreshing Squash - Neha Thasleem S P; Dr. A. Swaroopa Rani; H. Kavitha; G. Dileep; Dr. Kiran Kumar.A (The Bioscan, 2024)
Squash beverages are drinks produced by blending concentrated fruit syrup with water to create pleasant refreshment. These drinks are appreciated for their refreshing taste and the ability to customize them by varying the amount of syrup added. They are a pleasant tasty thirst quenching option and are enjoyed by various different age groups. The focus of this investigation is the creation of an innovative beverage, a guava mint Basil squash sweetened with honey, a natural alternative to processed sugars. Guava is a powerhouse of nutrition, boasting high levels of antioxidants, vitamin C, potassium, and dietary fiber, all contribute to its numerous health benefits. The study examines the sensory attributes, physical and chemical constituents, and the shelf life of the product’s freshness. A series of blends have been made and put through a rigorous assessment to gauge their flavor, scent, hue, pH level, acidity, sugar content, colour measurement and bacterial purity. Storage studies were carried out up to one week and the result showed that selected sample were in good condition after one month, though little bit of faded colour was found at the end of storage periods. Sample with40% sugar syrup, 50% guava pulp, 5% mint paste and 5% basil paste secured the highest score on sensory attributes. The research findings reveal that honey not only improves the taste experience but also preserves the healthful attributes of the squash. Moreover, the beverage shows commendable preservation of retention over time. The research enriches the range of health-oriented beverages and illuminates the use of natural sweeteners in beverage innovations.